Enhancement of positron yields using multi-layer targets irradiated by laser-induced energetic electrons - Peng, Meng; Ma, Yan-Yun; Li, Bo-Yuan; Tian, Li-Chao; Jiang, Jing; Zi, Ming; Yang, Xiao-Hu (Frontiers in Physics, 2022)
Positrons with high energy and shot pulse duration generated by ultra-short and ultra-intense laser interaction with two-target system (under-density plasma target and high-Z metal target) have wide applications. In this paper, we proposed an optimal scheme for enhancing positrons with multi-layer high-Z converters. Positrons with larger divergence escape from the target zone, reducing positron annihilation in the target, while those secondary particles with smaller divergence react with the subsequent target to produce more positrons. The total positron yield and positron beam divergence increased obviously with the target number when using the thin converter, while the scenario was reversed for the recorded positrons. The total positrons produced by bilayer 5 mm targets and 8-layer 1 mm targets increased by14%, 62%, respectively, compared to the outgoing positrons produced by 8 mm monolayer target. Positron yields can be further enhanced by adjusting the thickness of subsequent target and distance according to the intensity and angular distribution of positrons emitted from previous target.